Efektivitas Iklan Instagram @pt_transjakarta terhadap Perilaku Konsumen - Simanjuntak, Bintang Samuel; Aulia, Sisca (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Social media is becoming a key medium for promotional activities, including in the public transport sector such as Transjakarta. Instagram, as one of the most popular social media, provides a great opportunity for companies to convey their messages through interesting and innovative visual content. This research focuses on evaluating the effectiveness of Transjakarta advertisements on Instagram in influencing the behaviour of public transport users, especially among the younger generation. This research adopted a quantitative approach by applying a survey method involving 400 respondents, who were both followers and users of Transjakarta's official Instagram. The independent variables analysed included the visual appeal of the ad, the clarity of the message conveyed, the intensity of viewing, and user interaction. Meanwhile, the dependent variables include the level of awareness, satisfaction, loyalty, and decision to use Transjakarta services as a daily mode of transport. The collected data were processed using descriptive and inferential statistical analyses to explore the relationship between these variables. The research findings show that advertisements that are aesthetically appealing, informative, and encourage active user engagement can significantly increase awareness and influence the decision to use Transjakarta. Based on the results of this study, Transjakarta can strengthen digital marketing strategies with a focus on the younger generation, in order to increase the attractiveness of using public transport in Jakarta. Media sosial menjadi medium utama untuk aktivitas promosi, termasuk di sektor transportasi umum seperti Transjakarta. Instagram, sebagai salah satu media sosial yang paling digemari, menyediakan peluang besar bagi perusahaan untuk menyampaikan pesan mereka melalui konten visual yang menarik dan inovatif. Penelitian ini fokus pada evaluasi efektivitas iklan Transjakarta di Instagram dalam memengaruhi perilaku pengguna transportasi umum, terutama di kalangan generasi muda. Penelitian ini mengadopsi pendekatan kuantitatif dengan menerapkan metode survei yang melibatkan 400 responden, yaitu pengikut sekaligus pengguna Instagram resmi Transjakarta. Variabel independen yang dianalisis mencakup daya tarik visual iklan, kejelasan pesan yang disampaikan, intensitas penayangan, serta interaksi pengguna. Sementara itu, variabel dependen meliputi tingkat kesadaran, kepuasan, loyalitas, dan keputusan untuk menggunakan layanan Transjakarta sebagai moda transportasi sehari-hari. Data yang terkumpul diolah menggunakan analisis statistik deskriptif dan inferensial untuk mengeksplorasi hubungan antara variabel-variabel tersebut. Temuan penelitian menunjukkan bahwa iklan yang menarik secara estetika, informatif, dan mendorong keterlibatan aktif pengguna dapat secara signifikan meningkatkan kesadaran serta memengaruhi keputusan untuk menggunakan Transjakarta. Berdasarkan hasil penelitian ini, Transjakarta dapat memperkuat strategi pemasaran digital dengan fokus pada generasi muda, agar dapat meningkatkan daya tarik penggunaan transportasi umum di Jakarta.